Electronic, Raman and vibrational properties of AgmCun (m + n = 3-6) clusters: First principles study. Issue 1 (April 2019) - Li, Weiyin; Zhang, Yongli; Zhang, Sha; Hai, Lian; Ma, Wenqiang
Abstract: The electronic, Raman and vibrational properties of Ag m Cu n ( m + n= 3-6) nanoclusters were investigated using first principles. Results indicate that the electronegativity, hardness, softness, electrophilicity index, and energy gap vary with copper atom adding. Ag5 Cu1 cluster has the maximum energy gap and hardness, Ag1 Cu2 cluster has the maximum electronegativity, Ag2 Cu1 cluster has the maximum softness and electrophilicity index. Their Raman and vibrational spectra are related with their compositions, sizes, and geometries. As the amount of copper atom adds, the strongest Raman peaks of 3-6-atom silver-copper move large wavelength, and the strongest vibrational peaks of 3-atom, 5-atom (except Ag2 Cu3 ), and 6-atom (except Ag3 Cu3 ) silver-copper clusters also have a trend to shift large wavenumber. The wavenumber of the maximum vibrational peak of Ag3 Cu1 is the largest and the wavenumber of the maximum vibrational peak of Ag2 Cu2 is the smallest among the 4-atom silver-copper clusters.